Comparison of retrograde intrarenal surgery and percutaneous nephrolithotomy for the treatment of renal stones greater than 2 cm - Karakoç, Orhan (Turk J Urol, 2015)
OBJECTIVE: To evaluate the safety and efficacy of retrograde intrarenal surgery (RIRS) in the treatment of kidney stones greater than 2 cm and to compare its results with those of percutaneous nephrolithotomy (PCNL). MATERIALS AND METHODS: We retrospectively analyzed a total of 143 patients: 86 patients (53 males and 33 females) who underwent PCNL and 57 patients (37 males and 20 females) who underwent RIRS between October 2009 and October 2013. RESULTS: The mean duration of operation was 100.26±33.26 min in the RIRS group and 75.55±21.5 min in the PCNL group (p<0.001). The hospital stay was significantly shorter in the RIRS group (1.56±0.8 vs. 4.57±2.1 days in the RIRS and PCNL groups, respectively; p<0.001). Stone-free rates after one session were 66.6% and 91.8% of the RIRS and PCNL groups, respectively. The stone-free rate of the RIRS group improved to 87.7% after the second session. Blood transfusions were required in two patients in the PCNL group. Complication rates were higher in the PCNL group. CONCLUSION: This study revealed that RIRS can be an alternative to PCNL in the treatment of kidney stones with a diameter of 2–4 cm especially in patients with comorbidities.